EDUCATION VERSUS EXPERIENCE: WHICH MATTERS MORE FOR INDONESIAN BANK DIRECTORS? - Pangestu, Stevanus (Jurnal Manajemen, 2016)
The purpose of this paper is to assess the effects of board of directorsâ education and experience on firm financial performance. Based on the cross-sectional analysis of the involved 30 publicly-listed Indonesian banks, it is found that both directorsâ education and experience positively influence bank profitability, measured with Return on Assets ratio. The results of this study supports Hambrick and Masonâs Upper- Echelon theory. Based on the research findings, Indonesian banks are recommended to take experience and education into account when organizing board membersâwith more emphasis on the former due to the more impact it has. Furthermore, banks should also be encouraged to invest more in their human capital by facilitating further education of its board members.Keywords: Board Of Directors, Education, Experience, Firm Performance, Upper Echelon